Association between Increased Cataract Surgery Duration and Postoperative Outcomes. (4th March 2023) - Kalhorn, Ashton; Patnaik, Jennifer L; Ifantides, Cristos; Capitena Young, Cara E; Lynch, Anne M.; Christopher, Karen L
ABSTRACT: Purpose: To describe the relationship between surgical duration and post-operative outcomes in patients undergoing simple cataract surgery. Methods: This was a retrospective cohort study using data from the University of Colorado Department of Ophthalmology Cataract Outcomes Database. We studied eyes which underwent uncomplicated and non-complex cataract extraction via phacoemulsification between January 1, 2014 and December 31, 2018. Surgery duration was defined as "long" when greater than one standard deviation above the mean surgery time for a given surgeon. Post-operative variables were collected and outcomes were compared between the long surgery group and the non-long surgery group in univariate and multivariate analysis. Results: A total of 5839 eyes met criteria, of which 768 (13.2%) were classified as long surgeries. Multivariable analysis showed no association between prolonged postoperative inflammation and long surgeries (odds ratio [OR] 1.10, 95% Confidence Interval [CI] 0.64–1.91, p = .720). Long surgeries were associated with increased need for Nd:YAG capsulotomy (OR 1.42, 95% CI 1.10–1.82, p = .006). Post-operative day 1 visual acuity was poorer in the long surgery group (logMAR difference 0.03, 95% CI 0.01–0.06, p = .018) as was best-corrected visual acuity at post-operative month 1 through 3 (logMAR difference 0.02, 95% CI 0.01–0.04, p = .009). Conclusion: It may be beneficial for patients who have undergone long cataract surgery to be counseled on a slower visual recovery and on the greater likelihood of posterior capsular opacification. However, most outcomes of non-complex, non-complicated surgeries more than one standard deviation above the mean surgery length can be expected to be similar to surgeries of shorter length.